Textbook As A Medium of Interaction and Learning In English Language Learning; Qualitative Systematic Review - Muhammad Sulthon Ubaidillah; Daviq Rizal (Journal of English Language Studies, 2023)
Although technological advances offer new and advanced tools for language learning, language textbooks are the main means that are still used in language learning by world language learners and have become their target culture. This study aims to analyze the advantages of language textbooks to determine how effectively they are used as learning media and to examine their role in interactions while learning English. In this research, the researcher used the qualitative systematic review method by taking several references from journal articles to complement research data through a web database and using interviews as reinforcement and support. This study found that textbooks play a very important role in modern education, as demonstrated by the journal articles that researchers examined. Moreover, textbooks offer several advantages: first, they serve as a means to teach morals and pedagogy in English; second, they facilitate contextual interaction between educational components, with practical, authentic, and valid materials presented; and third, they help develop intercultural competence by promoting four key values: respect for diversity, respect for the rights of indigenous peoples, peace with the environment and all living things, and respect for cultural artifacts.